A Comparison of the Energy Expenditure in Different Storage Tank Geometries to Maintain H2 in the Liquid State - Joaquim Monteiro; Leonardo Ribeiro; Gustavo F. Pinto; Adélio Cavadas; Beatriz Coutinho; Andresa Baptista (Energies)
The aim of this paper is the study of the storage of hydrogen in the liquid state, LH2, with a focus on the thermal gains for cylindrical and spherical tank geometries. A given tank volume was assumed; three geometries for such a tank were taken, similar to the most common tanks for LH2 storage: cylindrical (vertical and horizontal) and spherical. An integrated refrigeration system was considered for LH2 stored at a temperature around 22 K and at a pressure around 3 bar. Then, the energy expenditure by the refrigeration system to maintain LH2 in the liquid state was determined and compared with the value of the energy contained in the LH2, in order to compare such a storage method to other hydrogen storage methods, namely compressed hydrogen, in the gaseous state. The most important conclusion was that spherical tanks had lower thermal gains than tanks with other geometries.